La mise en œuvre de la politique Trame verte et bleue en zone rurale aux échelles infrarégionales L’exemple de la basse vallée du Salat (Midi-Pyrénées, France) - Mathilde Canard; Jean-Marc Antoine; Sylvie Guillerme (VertigO)
The Green and Blue corridors policy (called Trame Verte et Bleue [TVB] in French), implemented in 2007 in France after the Grenelle Environment Forum, aims to preserve biodiversity by maintaining ecological continuities. Beyond the protected areas, it concerns also the areas of "ordinary biodiversity". Green and Blue corridors have to be deployed at the various territorial levels according to the principle of subsidiarity. This article focuses on the implementation of this policy in rural areas and at sub-regional levels. The case study of the lower valley of the Salat river (Occitanie region, France) is presented. It questions the appropriation of the Green and Blue corridors policy at different scales - from the project areas level up to the local level - through an analysis of the stakeholders discourse (professional bodies, local elected officials, farmers, individuals, local associations). First, this article shows that the territorial structures address the Green and Blue corridors policy through the prism of issues that are not necessarily focused on the preservation of biodiversity, leading to appropriate strategies in the territories. At the local scale, we see that the Green and Blue corridors policy is not well known and often misunderstood by the stakeholders. We also highlight the different levers used by territorial structures in charge of the Green and Blue corridors implementation to act locally, on public and private areas. Finally, it appears that the landscape entry chosen by some operators to implement this policy helps mobilize local stakeholders and influence their practices.